2016
DOI: 10.1371/journal.pone.0166951
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Uptake of an Extended Seasonal Malaria Chemoprevention Programme in Ghana: A Qualitative Study of Caregivers and Community Health Workers

Abstract: BackgroundSeasonal Malaria Chemoprevention (SMC) is currently recommended for children under five in areas where malaria transmission is highly seasonal. We explored children’s caregivers’ and community health workers’ (CHWs) responses to an extended 5-month SMC programme.MethodsThirteen in-depth interviews and eight focus group discussions explored optimal and suboptimal ‘uptake’ of SMC to examine facilitators and barriers to caregivers’ uptake.ResultsThere did not appear to be major differences between careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 25 publications
(31 reference statements)
4
41
0
Order By: Relevance
“…Community health workers and volunteers see themselves as agents of change who accompany the members of the community as they change their lives [ 18 ]. They use their local knowledge to explain health in simple terms and can address traditional false beliefs [ 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Community health workers and volunteers see themselves as agents of change who accompany the members of the community as they change their lives [ 18 ]. They use their local knowledge to explain health in simple terms and can address traditional false beliefs [ 14 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, an evaluation of the uptake of a malaria programme found that there were no differences in the knowledge, perceptions or understanding of the chemoprevention offered between those who took up the programme and those who had suboptimal uptake. The facilitators of uptake were rather the trust that the caregivers had for the medical experts and CHWs, the community networks that reinforced the usefulness of the programme and the learnt trust of those who were in the programme [ 18 ]. Trust is determined by the values of cooperation, empathy and open communication and was the basis of defining (in the eyes of the community) a good or bad health worker [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that societies that emphasize governmental responsibility for health may take low personal responsibility for protective measures and have increased passivity in terms of control [ 47 ], thereby burdening society with the cost of treating malaria. While promoting personal responsibility for general health is a well-developed approach, there is limited little research investigating its effectiveness for malaria prevention, other than a study identifying that most malaria preventive practices are personal measures (diligent bed net use, protective clothing), and that taking personal responsibility for malaria prevention empowers people to protect themselves [ 48 ]. The demand by participants for educational interventions targeted towards the most disadvantaged areas aligns with significant evidence suggesting education can increase personal responsibility for malaria prevention [ 49 ], with the probability of dying from malaria inversely related to education and income [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Having an empathetic, caring, and trusting relationship with the community is considered fundamental to the workers' success. 11,14,15,[20][21][22][23] Trust comes from CHWs being embedded in the community-that is, an "insider"-whom community members identify with and have confidence in. 13,14 Being an insider also means that CHWs understand and are direct witnesses to communities' needs and challenges and are well placed to know how to address them.…”
Section: Introductionmentioning
confidence: 99%